The Bad Guys in mission unpluckable - Blabey, Aaron (New York, NY : Scholastic Inc., 2017)
Still yearning to be seen as heroes, Wolf, Shark, Snake, and Piranha set out to rescue ten thousand chickens from a high-tech cage farm--but one unexpected problem is Mr. Snake himself, also known as "The Chicken Swallower."
School Library Journal starred
School Library Journal starred, January 2017
3.0
3-6
3-6
Keywords: Animals -- Comic books, strips, etc. -- Juvenile fiction; Chickens -- Comic books, strips, etc. -- Juvenile fiction; Heroes -- Comic books, strips, etc. -- Juvenile fiction; Rescues -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Fiction; Chickens -- Fiction; Heroes -- Fiction; Rescues -- Fiction; Animals -- Comic books, strips, etc. -- Fiction; Chickens -- Comic books, strips, etc. -- Fiction; Heroes and heroines -- Comic books, strips, etc. -- Fiction; Rescue work -- Comic books, strips, etc. -- Fiction; Graphic novels; Humorous comics